The efficacy of limited endoscopic sphincterotomy plus endoscopic papillary balloon dilation for removal of common bile duct stones in elderly patients - Vinh, Khanh; Nguyen, Van Thinh (Tạp chí Y Dược Huế, 2026)
Background: Bile duct stones are prevalent in tropical regions, including Vietnam, and can lead to serious complications such as cholangitis, septic shock, and mortality. The treatment of common bile duct (CBD) stones through endoscopic retrograde cholangiopancreatography (ERCP) has significantly enhanced the management of bile duct stones, resulting in reduced complications and facilitating quicker recovery, particularly in elderly patients. Methods: This study is a cross-sectional descriptive analysis involving follow-up on 34 patients (≥ 60 years) diagnosed with common bile duct (CBD) stones who underwent ERCP. Results: The stone clearance rate was 97.1%. Larger stones (≥ 20mm) had a lower success rate than smaller stones. The overall complication rate was 14.7%, with the most common being self-limiting bleeding after Oddi sphincterotomy. The average hospital stay after ERCP was 5.53 ± 3.33 days. Conclusion: Limited endoscopic sphincterotomy plus endoscopic papillary balloon dilation during ERCP is a minimally invasive, effective, and safe technique for elderly patients with CBD stones.